Towards a framework for enhancing procurement and supply chain management practice in the NHS: lessons for managers and clinicians from a synthesis of the theoretical and empirical literature - Joe Sanderson; Chris Lonsdale; Russell Mannion; Tatum Matharu (National Institute for Health Research, 2015)
Background: This review provides intelligence to NHS managers and clinicians involved in commissioning and procurement of non-pay goods and services. It does this in the light of ongoing pressure for the NHS to save money through a combination of cost cutting, productivity improvements and innovation in service delivery, and in the context of new commissioning structures developing as a result of the Health and Social Care Act 2012 (Great Britain. Health and Social Care Act 2012. Chapter 7. London: The Stationery Office; 2012). Objectives: We explore the main strands of the literature about procurement and supply chain management (P&SCM); consider the extent to which existing evidence on the experiences of NHS managers and clinicians involved in commissioning and procurement matches these theories; assess how the empirical evidence about different P&SCM practices and techniques in different countries and sectors might contribute to better commissioning and procurement; and map and evaluate different approaches to improving P&SCM practice. Review method: We use a realist review method, which emphasises the contingent nature of evidence and addresses questions about what works in which settings, for whom, in what circumstances and why. Adopting realist review principles, the research questions and emerging findings were sense-checked and refined with an advisory group of 16 people. An initial key term search was conducted in October 2013 across relevant electronic bibliographic databases. To ensure quality, the bulk of the search focused on peer-reviewed journals, though this criterion was relaxed where appropriate to capture NHS-related evidence. After a number of stages of sifting, quality checking and updating, 879 texts were identified for full review. Results: Four literatures were identified: organisational buying behaviour; economics of contracting; networks and interorganisational relationships; and integrated supply chain management (SCM). Theories were clustered by their primary explanatory focus on a particular phase in the P&SCM process. Evidence on NHS commissioning and procurement practice was found in terms of each of these phases, although there were also knowledge gaps relating to decision-making roles, processes and criteria at work in commissioning organisations; the impact of power on collaborative interorganisational relationships over time; and the scope to apply integrated SCM thinking and techniques to supply chains delivering physical goods to the NHS. Evidence on P&SCM practices and techniques beyond the NHS was found to be highly fragmented and at times contradictory but, overall, demonstrated that matching management practice appropriately with context is crucial. Conclusions: We found that the P&SCM process involves multiple contexts, phases and actors. There are also a wide variety of practices that can be used in each phase of the P&SCM process. Thinking about how practice might be improved in the NHS requires an approach that enables the simplification of the complex interplay of factors in the P&SCM process. Portfolio-based approaches, which provide a contingent approach to considering these factors, are recommended. Future work should focus on conflicting preferences in NHS commissioning and procurement and the role of power and politics in conflict resolution; the impact of power on the scope for collaboration in health-care networks; and the scope to apply integrated SCM practices in NHS procurement organisations. Funding: The National Institute for Health Research Health Services and Delivery Research programme.